The Role of Leadership, Motivation, and Work Discipline in Increasing Employee Commitment at CV Dwi Kurnia Mandiri, Purwokerto - Harries Madiistriyatno (Mandalika Journal of Business and Management Studies, 2025)
This study aims to analyze the research approach using qualitative methods with data collection techniques in the form of in-depth interviews, observations, and documentation. The research informants consisted of leaders and employees who were selected purposively to gain a deep understanding of organizational dynamics. The results of the study show that participatory leadership style, consistent motivation, and the implementation of fair and transparent work discipline have a significant influence on increasing employee commitment. This study recommends the development of leadership training programs, performance-based rewards, and consistent enforcement of work rules to strengthen employee commitment. This finding is expected to make a practical contribution to the management of CV Dwi Kurnia Mandiri in creating a productive and harmonious work environment.